LRRK-2 as a Key Molecule Bridging Inflammation to Parkinson's Disease - Roca, Valeria Ines (2013)
The pathogenetic mechanisms leading to typical Parkinson's Disease (PD), the second most common human neurodegenerative disorder remains unknown. Genetic variants of Leucine-Rich Repeat Kinase 2 (LRRK-2) are associated with a significantly enhanced risk for PD. The discovery that late-onset PD could be caused by the inheritance of a mutation in the LRRK-2 gene leading to familial as well as sporadic forms of PD has provided researchers an opportunity to explore the pathophysiological events underlying this complex disease. Despite extensive research our understanding of LRRK-2 biological function and regulation remains rudimentary. In this review, we give an insight into the role of LRRK-2 in modulating inflammation in the central nervous system and we hypothesize that LRRK-2 dysfunction may favor the neurodegenerative process observed in PD.